2017
DOI: 10.1016/j.syapm.2017.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetically diverse group of native bacterial symbionts isolated from root nodules of groundnut ( Arachis hypogaea L.) in South Africa

Abstract: Groundnut is an economically important N​2-fixing legume that can contribute about 100–190 kg N ha−1 to cropping systems. In this study, groundnut-nodulating native rhizobia in South African soils were isolated from root nodules. Genetic analysis of isolates was done using restriction fragment length polymorphism (RFLP)-PCR of the intergenic spacer (IGS) region of 16S-23S rDNA. A total of 26 IGS types were detected with band sizes ranging from 471 to 1415 bp. The rhizobial isolates were grouped into five main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 55 publications
3
23
0
2
Order By: Relevance
“…Multiple alleles in the rRNA operon of bacteria account for spacer variations between and among species and can be used for typing and identification of rhizobial species ( 38 ). The ITS ribosomal genes have been shown to be good markers for assessing rhizobial diversity ( 16 ). In this study, ITS-PCR analysis grouped the 99 rhizobial isolates into 17 distinct ITS types, which showed very high polymorphism (258 to 1,350 bp) within the ITS region of the rhizobial genomic DNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple alleles in the rRNA operon of bacteria account for spacer variations between and among species and can be used for typing and identification of rhizobial species ( 38 ). The ITS ribosomal genes have been shown to be good markers for assessing rhizobial diversity ( 16 ). In this study, ITS-PCR analysis grouped the 99 rhizobial isolates into 17 distinct ITS types, which showed very high polymorphism (258 to 1,350 bp) within the ITS region of the rhizobial genomic DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Such studies are important for generating a genetic resource base from which highly adapted and efficient rhizobial strains are selected for inoculant production ( 15 ). Therefore, well-tested, quick methods are required for differentiating rhizobial isolates ( 16 ). PCR of the BOX element (BOX-PCR) and PCR-restriction fragment length polymorphism (RFLP) analyses have become powerful tools for detecting diversity among rhizobial isolates at the genome level ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of the almost complete sequence (1268 nt) of the 16S rRNA gene of strain ESA 123 showed that this isolate is classified within the B. japonicum clade with the most similarity to the strain type 14-3 T B. kavangense. This species has recently been described, isolated from peanut nodules in Namibia (Grönemeyer et al 2015) and bacteria with sequences of the 16S rRNA gene related to B. kavangense were later isolated in South Africa (Jaiswal et al 2017) and in Brazil (Santos et al 2017a). Although the 16S rRNA gene sequence shows high similarity (98.97%) to B. kavangense, the ESA 123 strain may represent a new species, since the taxonomy of Bradyrhizobium is complex and cannot be elucidated only with the 16S rRNA allele (Hungria et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Los genes nifH se encuentran diversificados y su transcripción está controlada por la ARN polimerasa, que es una holoenzima alternativa, y también necesita una proteína activadora nifA (Satyanarayana, Krishna, Pavan, & Jeereddy, 2018). Otros genes identificados por PCR son 16S rRNA (Akemi et al, 2017;Jaiswal, Msimbira, & Dakora, 2017;Tahon & Willems, 2017), porque permite una clasificación filogenética más detallada a nivel de especie (Osei, Abaidoo, Ahiabor, & Boddey, 2018;Ribeiro et al, 2018), genes rec A, atpD, gln II y nod C con análisis de secuencia multilocus (MLSA) (Leite et al, 2017;Mwenda, Hara, De Meyer, Howieson, & Terpolilli, 2018;Rigonato et al, 2017). Con esta técnica, se ha logrado identificar el gen nifH en géneros Paenibacillus, Enterobacter, Klebsiella y Pantoea (Ndungu et al, 2018), que no son reconocidos por fijar nitrógeno, de modo que es posible que hayan obtenido la capacidad de fijación de nitrógeno a través de la transferencia lateral de genes; sin embargo, las fuerzas evolutivas de la transferencia lateral de genes no son bien conocidas (Khalifa & AlMalki, 2018).…”
Section: Técnicas Pcr Identificación De Los Genes Nifhunclassified